PENGAWETAN SEPULUH JENIS KAYU SECARA RENDAMAN DINGIN - Emmy Yetty; Barly Barly (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The result of cold soaking treatment of ten wood species is reported in this paper. Five wood species are recommended for housing (agatis, balsa, damar kaca, karet and kemayau), whereas the other five species (begontoi, belangeran, kenari I, kenari II and mahoni) could not meet the spesification. Solution concentration of Koppers Formula 7 preservative used was 10 percent with soaking period of one, three and five days. The treatment shchedule proposed for five wood species is also presented in this paper.